The Effects of the Introduction Syariah Index To the Bursa Malaysia Stock Index and Bursa Malaysia Stock Index Futures - Ahmad, I.; Abdul Rahim, F.; Pyeman, J.; Asmaddy Haris (Universiti Sains Islam Malaysia, 2024)
This study tries to investigate the effect of introduction of Syariah Index to the price relationships and volatility transmissions between the Bursa Malaysia stock Index and Bursa Malaysia Stock Index Futures. In addition, it also tries to find the relationships between Bursa Malaysia Stock Index, Bursa Malaysia Stock Index Futures and Syariah Index. Vector Autoregression (VAR) GJR-GARCH model was applied to nine years daily price of the variables investigated. The results present evidence that the introduction of Syariah Index has changed the price relationships and volatility transmissions between the spot and futures markets in Malaysia. Furthermore, the findings of this study show that the there are feedback effects in the price relationships between the investigated. The findings also suggest that Bursa Malaysia Stock Index is the main information producer in predicting and analyzing the volatility of Bursa Malaysia Stock Index Futures and Syariah Index. Finally, the overall conditional correlation estimates between the three variables investigated are higher in the unrestricted model form compared to the restricted model form.